PAK dan Teologi Martabat Manusia:: Integrasi Imago Dei dalam Moralitas dan Etis Generasi Muda - Rahayu, Yohana Fajar; Sumual, Elisa Nimbo; Arifianto, Yonatan Alex (Sekolah Tinggi Teologi Real Batam, 2025)
Abstract: The moral crisis and decline in human values affecting the younger generation demand a renewal in educational approaches, particularly in Christian religious education. Education that focuses solely on cognitive and doctrinal aspects has proven insufficient in shaping the character and ethical awareness of students in a holistic manner. The absence of a strong theological foundation in the design of Christian religious education has caused the educational process to lose its transformative power. The phenomenon of the decline in human values and morality, and the loss of empathy among the younger generation, reinforces the urgency of a more humanistic and spiritual approach. This study aims to integrate the values of Imago Dei into the design of moral learning as a form of implementing the theology of human dignity in Christian religious education. Using a descriptive qualitative method with a literature review approach, it can be concluded that the Imago Dei as the theological foundation of moral education must be strong to prevent a moral crisis among the younger generation, as this is a contextual challenge for Christian religious education in this era. The need to integrate the theology of human dignity into moral education design will bring a more humanising face to Christian religious education. This serves as an ethical and pastoral implication for the church and school. Abstrak: Krisis moralitas dan nilai kemanusiaan yang melanda generasi muda menuntut adanya pembaharuan dalam pendekatan pendidikan, khususnya dalam PAK. Pendidikan yang hanya berfokus pada aspek kognitif dan doktrinal terbukti tidak cukup membentuk karakter dan kesadaran etis peserta didik secara utuh. Ketidakhadiran fondasi teologis yang kuat dalam desain pembelajaran PAK menjadikan proses pendidikan kehilangan daya transformatifnya. Fenomena dekadensi nilai kemanusiaan dan moralitas, dan hilangnya empati di kalangan generasi penerus, memperkuat urgensi pendekatan yang lebih humanistik dan spiritual. Penelitian ini bertujuan untuk mengintegrasikan nilai-nilai Imago Dei dalam desain pembelajaran moralitas sebagai bentuk implementasi teologi martabat manusia dalam PAK. Menggunkan metode kualitatif deskriptif dengan pendekatan studi pustaka maka dapat dinyatakan kesimpulan bahwa imago dei sebagai dasar teologis pembelajaran moral dalam PAK harus kuat supya tidak terjadi krisis moralitas di generasi muda, sebab ini adalah tantangan kontekstual pendidikan agama Kristen di era ini. perlunya integrasi teologi martabat manusia dalam desain pembelajaran moralitas akan membawa wajah PAK yang memanusiakan. ini sebagai bagian implikasi etis dan pastoral bagi gereja dan sekolah.